Summer Rental - Reiner, Carl, 1922-; Candy, John.; Joseph Lawrence; Karen Austin; Kerri Green (USA Paramount Pictures, 1985)
Jack Chester, an overworked air traffic controller, takes his family on vacation to the beach. Things immediately start to go wrong for the Chesters, and steadily get worse. Jack ends up in a feud with a local yachtsman, and has to race him to regain his pride and family's respect.
Jack Chester, an overworked air traffic controller, takes his family on vacation to the beach. Things immediately start to go wrong for the Chesters...
Mark Reisman
Languages : English, German, French, Spanish, Italian Subtitles : English, Turkish, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese, Danish, Finnish, Greek, Hindi, Hungarian, Icelandic, Norwegian, Polish, Romanian, Swedish, Arabic, Bulgarian, Hebrew
Keywords: Comedy